2022
DOI: 10.3390/antibiotics11060787
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Activity of Dermaseptin through Its Immobilization on Alginate Nanoparticles—Effects of Menthol and Lactic Acid on Its Potentialization

Abstract: Dermaseptin B2 (DRS-B2) is an antimicrobial peptide secreted by Phyllomedusa bicolor, which is an Amazonian tree frog. Here, we show that the adsorption of DRS-B2 on alginate nanoparticles (Alg NPs) results in a formulation (Alg NPs + DRS-B2) with a remarkable antibacterial activity against Escherichia coli ATCC 8739 and E. coli 184 strains, which are sensitive and resistant, respectively, to colistin. The antibacterial activity, obtained with this new formulation, is higher than that obtained with DRS-B2 alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Combining DRS-B2 with alginate nanoparticles (Alg NPs) results in a formulation (Alg NPs + DRS-B2) that creates novel B2 derivatives displaying significant antibacterial efficiency against both susceptible and resistant strains of Escherichia coli to colistin. The antibacterial activity achieved with this innovative formulation exceeds that of DRS-B2 when used alone [ 26 ]. Moreover, our synthesized peptides offer the advantage of being configured with D-amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Combining DRS-B2 with alginate nanoparticles (Alg NPs) results in a formulation (Alg NPs + DRS-B2) that creates novel B2 derivatives displaying significant antibacterial efficiency against both susceptible and resistant strains of Escherichia coli to colistin. The antibacterial activity achieved with this innovative formulation exceeds that of DRS-B2 when used alone [ 26 ]. Moreover, our synthesized peptides offer the advantage of being configured with D-amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Sruthy et al [ 57 ] confirmed that at the highest tested concentration of histone H2A-derived antimicrobial peptide (200 μM), growth inhibition of 89% was observed in HEp2 cell lines. Another study conducted by Hazime et al [ 26 ] tested the cytotoxic effects of DRS-B2 and of a new formulation (Alg NPs + DRS-B2) on the human erythrocytes and eukaryotic cell line types HT29 (human) and IPEC-1 (animal); in that study, their safety was verified. Zairi et al [ 58 ] found that dermaseptin K 4 S4 exhibited an enhanced toxicity profile against human endometrial epithelial cells, displaying lower sensitivity to the toxic effects of dermaseptins compared to other cell types.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their biocompatibility and biodegradability, natural polymers, including chitosan, alginate, and albumin, have been investigated as drug carriers [88][89][90][91][92][93][94][95][96][97]. For example, ceftriaxone-loaded chitosan tripolyphosphate nanoparticles exhibited enhanced antibacterial effects against intracellular S. typhimurium (Salmonella typhimurium) than the inefficient free drug [98].…”
Section: Antibiotic-loaded Polymeric Nanoparticlesmentioning
confidence: 99%